PENGARUH PRODUCT PLACEMENT KOPIKO (MEREK LOKAL) PADA DRAMA KOREA VINCENZO TERHADAP SIKAP PENONTON INDONESIA (Survei Pada Followers Akun Twitter @kdrama_menfess) - Cindy Farida Sitorus (2022)
Indonesian original products are present in the middle of the storyline of the Korean drama Vincenzo. The product placement is widely discussed on social media, one of them is Twitter. The increasing number of Korean drama viewers has resulted in the formation of a Korean drama lovers community network (fanbase) on Twitter that actively shares information and provides feedback regarding Korean dramas. This study aims to see how the shift in advertising strategy by using product placement is applied to Korean dramas. The research focuses on how positive the attitude of Indonesian audiences after seeing the placement of local brand in South Korean television programs. The country of origin where the product is produced able to influence the attitude of the audience. To analyze this research, the AISAS model was used. This research uses quantitative research methods with explanative research type. In collecting data, this study uses a questionnaire distributed to 100 respondents. The results showed that although there is an influence between Kopiko's product placement in the Korean drama Vincenzo about 24% on the attitudes of Indonesian audiences, the conative aspect of Indonesian audience attitudes in this study has not been seen. Researchers suggest that future researchers can conduct more in-depth research on variables or other factors that have not been studied with a different point of view.